Inmigración venezolana y estigmatización laboral en el Perú - Loayza, Jerjes (2020)
Venezuelan migration, to this day, is the most impressive migratory event in the future of Peruvian history due to its high number. Intersubjectivities are studied during the years 2017 to 2019, with special emphasis on the study of the body and migrant emotions inserted in the exchange of subjective evaluations. For this, in-depth interviews, stories and memories of life are applied to migrant women and men of Venezuelan nationality in the cities of Lima, Ayacucho, Chiclayo and Cusco. Grudges, confrontations and prejudices between Peruvians and Venezuelans are recognized, which are promoted by the media. The clash of customs, thoughts and beliefs would include outbreaks of xenophobia and patriarchalism that, although it would cause the radicalization of inequality, must be understood in the already known dynamics of discrimination and violence against women that had been developing in Peru in a structural way. Finally, the perseverance of the Venezuelan migrant to reinvent new dynamics that seek Peruvian acceptance for their labor insertion in the country stands out.